Pembelajaran digital storytelling berbasis nearpod di sekolah dasar 68/VI Empang Benao - Alfiana, Rinta; Maryono, Maryono; Al Fath , Ayatullah Muhammadin (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
Digital technology has led to the emergence of various innovations in learning, one of which is digital storytelling, which is believed to optimize writing skills as well as the learning motivation of elementary school students. This study aims to systematically examine the role of digital storytelling in the context of primary education, focusing on the development of writing skills, the enhancement of motivation, and its contribution to classroom collaboration. The method used is a systematic literature review by selecting and analyzing relevant scientific articles from both international and national journals. The synthesis results show that digital storytelling consistently has a positive impact on the quality of students’ writing, including narrative structure, creativity, and text cohesion. In addition, this technology has been proven to optimize learning motivation through more interactive, contextual, and meaningful experiences, as well as to support collaborative skills by encouraging interaction and cooperation among students. The findings also reveal variations in effectiveness depending on the platforms used, where Nearpod and similar media provide easier integration in the classroom and higher student engagement. This article contributes by presenting a conceptual and empirical synthesis of the implementation of digital storytelling, while offering a foundation for teachers, curriculum developers, and researchers to adopt this approach as an innovative strategy to improve the quality of writing education in primary schools. In conclusion, the integration of digital storytelling with Nearpod demonstrates high validity, practicality, and effectiveness in enhancing writing skills and learning motivation among elementary school students, providing a valuable model for digital pedagogy and practical strategies for educators.